MENINGKATKAN HASIL BELAJAR SISWA TENTANG KONSEP JARINGAN TUMBUHAN MELALUI MODEL PEMANCAR PADA SISWA KELAS XI IPA 3 SMAN 1 SAMPARA - Ferdinan Lekman (Program Studi Akuntansi IKOPIN, 2021)
This research is a Classroom Action Research in an effort to improve studentlearning outcomes about the concept of plant tissue through the use of amicroscope, android, note book and chart (transmitter) which is an acronym forthe sentence use of a microscope, android, note book and chart. The aims of thisresearcher are to: (1) Improve student learning outcomes about plant tissueconcepts through the use of microscopes, androids, note books and charts in classXI IPA 3 SMA Negeri 1 Sampara odd semester 2017-2018 school year, (2 )Increase student learning activities about the concept of plant tissue through theuse of microscopes, androids, note books and charts in class XI IPA 3 SMANegeri 1 Sampara in odd semesters in the 2017-2018 learning year, (3) Increaseteacher teaching activities about network concepts through the use of amicroscope , android, note books and charts in class XI IPA 3 SMA Negeri 1Sampara odd semester 2017-2018 learning year. The formulation of the problemin this study is